Uji Aktivitas Antibakteri Ekstrak Akar Kuning (Arcangelisia Flava Merr.) Terhadap Bakteri Escherichia Coli - Siti Marita Ubaid; Zakiyatul Hamidah; Erliyananda Pretty Desi; Panji Ratih Suci; Ismu Dwi Supangkat (Pusat Riset dan Inovasi Nasional, 2024)
Arcangelisia flava Merr, which has been known empirically by the Dayak community in Central Kalimantan as natural herbs. This study aimed to determine the antibacterial effect of the Arcangelisia flava Merr extract against Escherichia coli. This study used two concentration of 25% and 50%, Ciprofloxacin as a positive control and water for injection as a negative control. The existence of the effect of the Arcangelisia flava Merr. extract against bacteria Escherichia coli is characterized by the formation of inhibition zone at a concentration of 25% obtained by the mean 2,005 mm, concentration of 50% obtained by the mean 2,435 mm, positive control obtained mean 7,975 mm, while for the negative control has no effect on Escherichia coli. The results showed that the Arcangelisia flava Merr. can significantly inhibit the growth of Escherichia coli bacteria. And there was the tendency of an increase in the concentration of Arcangelisia flava Merr. The higher concentration of Arcangelisia flava Merr. Extract the higher the resulting inhibit zone.